Consideration of financial and environmental concerns in the life cycle costing of higher education's facilities and services: a systematic review of one decade - Wafa, Wafaurahman; Sharaai, Amir Hamzah; Matthew, Nitanan Koshy; Akhundzada, Noor Ahmad (Human Resource Management Academic Research Society, 2024)
The lack of life cycle costing (LCC) studies in higher education is knowledge gap and literature. This paper aimed to review the components that made up the life cycle cost for higher education. This systematic review focused on LCC of Higher Education, where review articles and research articles were collected from Springer-Link, Science-Direct, Scopus, and Google-Scholar online databases. Considering the PRISMA statement and guideline for systematic review in conservation and environmental management. The literature reviewed systematically and bibliometric analysis of co-authorship and concurrence of keywords were analyzed by VOSviewer software. The result shows that there is various studies written about LCC of products, and a deficit of studies in the application of LCC in higher education. Furthermore, there are some studies that used the LCC in construction that were calculated based on the NPV in educational buildings. The most cost element and components were the constructions, operations, maintenances, and demolition. Furthermore, the environmental LCC was used alongside LCA. LCA mostly focused on environmental externalities cost for supporting sustainability. The LCC of higher education is needed to be calculated, involving the total cost of a university as well as construction, operation, safety, externalities, and services costs. However, the education services, facilities and students’ costs calculations were not used in the literature. Therefore, it is recommended to establish a comprehensive method to estimate the cost of services and facilities of higher education altogether to contribute in sustainability.